Guía para organizaciones sociales: ¿Qué son y cómo funcionan las brigadas de recuperación y los bancos comunitarios de alimentos frescos recuperados? - Santandreu, A.; Tueroconza, E.; López, D.; Ninahuamán, J. (2025)
This guide documents the experience of community organizations in Peru in recovering fresh food from agricultural fields and wholesale markets to improve food security among vulnerable populations. Based on evidence generated between 2023 and 2025, it presents the operational model of food recovery brigades and community food banks that redistribute fresh, nutritious foods while reducing food loss and waste. The document highlights practical implementation steps, organizational arrangements, and regulatory considerations, demonstrating how community-led food recovery systems can strengthen urban and peri-urban food systems, enhance access to healthy diets, and contribute to more resilient and sustainable food systems.